Inflammatory Myofibroblastoma of the Breast: A Case Report - Wei, Ling; Jiang, Guoyuan; Bai, Lala; Li, Tingchao; Ma, Xuejin; Jiang, Lin; Wang, Jie; Li, Shiguang (Frontiers in Oncology, 2021)
Inflammatory myofibroblastic tumor (IMT) is a rare tumor with low-grade malignant risk mainly occurring in soft tissues and lung, and it’s extremely rare in the breast. Meanwhile, imaging findings of the tumor often presents with non-specific features that lead to misdiagnosis and delayed treatment. Here, we report a case of inflammatory myofibroblastic tumor in the breast with the imaging findings of mammography, magnetic resonance imaging(MRI), and pathologic findings to improve the understanding of the disease. The patient was treated by surgical operation, and was followed up for 44 months, no local recurrence and distant metastasis.